PENDIDIKAN MULTIKULTURAL DI SEKOLAH DASAR: SLR TERHADAP STRATEGI, PRAKTIK, DAN DAMPAKNYA TERHADAP TOLERANSI - Maharani Revenaya; Fathur Rokhman; Bambang Subali; Ellianawati Ellianawati (JS (JURNAL SEKOLAH), 2026)
Abstract: This study examines multicultural education in Indonesian elementary schools through a Systematic Literature Review (SLR) of 31 empirical studies published between 2015 and 2024. The findings indicate that multicultural education plays a strategic role in fostering tolerant, empathetic, and socially responsible students. Effective strategies include integrating multicultural values into the curriculum, strengthening inclusive school cultures, utilizing local wisdom, and involving the community. Practical implementation is reflected in interactive learning activities such as cross-cultural projects, local arts, and social initiatives. Multicultural education enhances social awareness, empathy, and national identity while reducing prejudice, although challenges remain in teachers’ competencies and policy consistency. Keyword: Multicultural Education, Primary School, Indonesia